Characterization of pysio-chemical properties of novel one stop chemical method in preparations of copper nanofluids and possible explanations - Leakath, Muhammad Zafran (2011)
Nanofluid is a dilute suspension containing particles in nanometer sized which are dispersed in the base fluid like ethylene glycol or water. Nanofluid is one of the crucial discovery in modern science which found to be having better thermal properties compared with conventional fluids like water or ethylene glycol thus makes it ideal to be applied and utilized in many areas in heat transfer area such as cooling, utilized as fluid for heat echangers and etc. Besides, the nanofluid with the improved thermal properties could solve the problem faced by various industries in the area of heat transfer. For example, in the semiconductor industry, the needs of superior cooling coolant are very crucialJn this paper, presents about preparation of copper nanofluid using novel one stop chemical method by reducing copper sulphate pentahydrate using reduction agent which is sodium hypophosphite in ethylene glycol as base fluids. The obtained nanofluid by using this novel one stop method is more stable besides cheaper and faster compared with two stop method whereby in the two step method, the production of the nanoparticles and the nanofluids are isolated. The process of drying, storage and transportation of the nanoparticles that takes place in two step method have cause the agglomeration and sedimentation of the nanofluids. As the result, the agglomeration could cause the settlement and clogging in the microchannel besides reduce the thermal conductivity. Therefore in the novel one stop method the production of the nanoparticles and the nanofluids are combined and not separated to avoid the process of drying, storage and transportation of nanoparticles. Meanwhile the nanofluid that obtained were analyzed using Transmission Electron Microscopy (TEM), UV-Vis Spectrophotometer, Viscometer and Fourier Transform Infared Spectroscopy (FTIR). The effect and influences of pH and dilution to the reaction rate and properties of nanofluid were also investigated.